2022
DOI: 10.1080/20002297.2022.2088936
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response of gut, spleen, and liver in mice induced by orally administeredPorphyromonas gingivalis

Abstract: Background Periodontitis is a chronic multifactorial inflammatory disease. Porphyromonas gingivalis is a primary periopathogen in the initiation and development of periodontal disease. Evidence has shown that P. gingivalis is associated with systemic diseases, including IBD and fatty liver disease. Inflammatory response is a key feature of diseases related to this species. Methods C57BL/6 mice were administered eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 76 publications
2
15
0
Order By: Relevance
“…39 Porphyromonas is associated with systemic diseases, evoking inflammation in the gut, spleen, and liver. 40 In our study, Rikenellaceae_RC9_-gut_group were negatively correlated with downregulated metabolites of arachidonic acid (11-HDoHE, dinoprost, 15keto prostaglandin F1α, TxB3, 11β-prostaglandin F2α, 8-iso prostaglandin F2α, 8-iso prostaglandin F2β), and Bile acids(Chaps), and positively correlated with the upregulated metabolites of bile acids (chenodeoxycholic acid, taurochenodesoxycholic acid), Porphyromonas was just the opposite. Enzymatically oxidized lipids, derived from the oxygenation of polyunsaturated fatty acids, such as arachidonic acid and bile acids, are produced in response to extracellular stimuli, which function in the resolution of inflammation and the immune response.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…39 Porphyromonas is associated with systemic diseases, evoking inflammation in the gut, spleen, and liver. 40 In our study, Rikenellaceae_RC9_-gut_group were negatively correlated with downregulated metabolites of arachidonic acid (11-HDoHE, dinoprost, 15keto prostaglandin F1α, TxB3, 11β-prostaglandin F2α, 8-iso prostaglandin F2α, 8-iso prostaglandin F2β), and Bile acids(Chaps), and positively correlated with the upregulated metabolites of bile acids (chenodeoxycholic acid, taurochenodesoxycholic acid), Porphyromonas was just the opposite. Enzymatically oxidized lipids, derived from the oxygenation of polyunsaturated fatty acids, such as arachidonic acid and bile acids, are produced in response to extracellular stimuli, which function in the resolution of inflammation and the immune response.…”
Section: Discussionsupporting
confidence: 50%
“…Rikenellaceae_RC9_gut_group promotes intestinal mucosal health and is positively correlated with host feed utilization rate and SCFA metabolism . Porphyromonas is associated with systemic diseases, evoking inflammation in the gut, spleen, and liver . In our study, Rikenellaceae_RC9_gut_group were negatively correlated with downregulated metabolites of arachidonic acid (11-HDoHE, dinoprost, 15-keto prostaglandin F1α, TxB3, 11β-prostaglandin F2α, 8-iso prostaglandin F2α, 8-iso prostaglandin F2β), and Bile acids­(Chaps), and positively correlated with the upregulated metabolites of bile acids (chenodeoxycholic acid, taurochenodesoxycholic acid), Porphyromonas was just the opposite.…”
Section: Discussionsupporting
confidence: 47%
“…More specifically, Porphyromonas gingivalis has been well-associated with the occurrence and development of gastrointestinal cancers. In mice orally administered Porphyromonas gingivalis , the mRNA levels of IFN-gamma were elevated in the gut ( 48 ). In CRC, Fusobacterium is associated with tumor carcinogenesis, high disease stage, poor tumor differentiation, poor prognosis ( 49 ) and metastatic disease ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, animal experiments have shown that systemic inflammation induces increases in spleen mass [18]. For example, repeated oral administration of Pg has been found to increase spleen weight in mice [19]. The spleen plays a crucial role in modulating immune responses by promoting the differentiation and activation of T and B cells.…”
Section: Introductionmentioning
confidence: 99%